Green Accounting and Different Perspective of Financial Performance - Triwacananingrum, Wijaya; 'Alim, Nur (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: This research aims to examine the effect of green accounting on company financial performance using quantitative methods. Method: This research uses quantitative methods with a descriptive analysis approach. Data analysis using multiple linear regression testing methods. The company's financial performance in this study was measured using Return on Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS). Meanwhile, the independent variable is the implementation of green accounting. Results: The results showed that green accounting has a positive and significant impact on financial performance as measured by ROA and EPS, while the measurement of financial performance did not affect ROE. Implications: this research is expected to serve as a reference for future researchers and as a consideration for investors and entrepreneurs in determining strategic steps in business. Novelty: This research elaborates on 260 samples from the Basic Material, Chemical, and Healthcare Sectors.